2007
DOI: 10.1038/sj.tpj.6500448
|View full text |Cite
|
Sign up to set email alerts
|

Rat survival to anthrax lethal toxin is likely controlled by a single gene

Abstract: We examined whether survival of different rat strains administered anthrax lethal toxin is genetically determined. A reproducible test population of first filial generation hybrid rats was bred based on the susceptibility of progenitors to anthrax lethal toxin and to maximize genetic diversity across the strains. These rats were then tested with varying doses of anthrax lethal toxin. We found that all 'sensitive' strains died within 2 h following systemic administration of 240 mg/kg lethal toxin, while one str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Genetic backcrossing experiments in rats further suggested that a dominant gene not only controlled LT killing in vitro, but also LT-mediated disease progression. 19 This in vitro and in vivo correlation in rats is clearly distinct from the murine system, where in vitro and in vivo LT susceptibilities do not correlate. 30,31 Based on these studies, we hypothesized that a dominant gene controls macrophage killing as well as vascular collapse in rats challenged with LT. To test this hypothesis we initially determined whether the inflammatory proteincaspase-1 controlled macrophage killing of susceptible rat macrophages.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Genetic backcrossing experiments in rats further suggested that a dominant gene not only controlled LT killing in vitro, but also LT-mediated disease progression. 19 This in vitro and in vivo correlation in rats is clearly distinct from the murine system, where in vitro and in vivo LT susceptibilities do not correlate. 30,31 Based on these studies, we hypothesized that a dominant gene controls macrophage killing as well as vascular collapse in rats challenged with LT. To test this hypothesis we initially determined whether the inflammatory proteincaspase-1 controlled macrophage killing of susceptible rat macrophages.…”
Section: Resultsmentioning
confidence: 92%
“…4,29 -31 Recent studies have indicated that LT susceptibility of rat macrophages is also strain-dependent and controlled by a single, dominant gene, potentially the rat homologue of murine Nalp1b. 19 Based on the similar LT susceptibility pattern of murine and rat macrophages, we predicted that LT killing of susceptible rat macrophages was also caspase-1-dependent. Genetic backcrossing experiments in rats further suggested that a dominant gene not only controlled LT killing in vitro, but also LT-mediated disease progression.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations